Effect of wearing the elevation training mask on physiological performance in elite kayaking girls - Ghram, A.; Amirshaghaghi, F.; Bragazzi, N. L.; Akbari, H. A.; Chtourou, H.; Lavie, C. J.; Jiménez-Pavón, D. (International Journal of Sport Studies and Health, 2021)
Background: The elevation training mask 2.0 (ETM) has been introduced as a novel tool to allow for respiratory muscle training and altitude exposure during exercise that can improve performance and hematological markers in elite and well-trained athletes. Objectives: The purpose of the present study was to examine the effect of wearing ETM while performing exercise training on erythropoietin (EPO), vascular endothelial growth factor (VEGF), peak oxygen consumption (VO2max), lactate, and 1000-m kayaking performance in elite Kayaking girls. Methods: Thirty elite Kayaking girls (14 to 18-year-old) were equally and randomly assigned into mask, no mask, and control groups. The mask and no-mask groups completed 8 weeks of repeated sprint training, while the control group performed their routine kayaking training programs. Pre- and post-training tests included EPO, VEGF, VO2max, lactate, and 1000-m kayaking performance. Results: We showed that 1000-m time trial significantly decreased for mask (P < 0.001) and control (P = 0.035) groups, and was significantly lower in mask group than control (P = 0.014) and no mask (P = 0.009) groups. EPO did not show any significant changes for all groups. VEGF was increased significantly for mask (P = 0.04) and no mask (P = 0.014) groups. Lactate was decreased significantly for mask group (P = 0.025). VO2max increased significantly for no mask group (P = 0.021). Conclusions: Performing repeated sprint training while wearing ETM has the potential to enhance performance in Kayak racing.